CREATION OF ECO-ART BASED ARTWORKS USING LOCAL BAMBOO MATERIALS IN SEMARANG - Sanjaya, Bangkit (Arty: Jurnal Seni Rupa, 2025)
Bamboo is a primary raw material in Indonesian society. Bamboo is used for everyday needs because it is easy to process. Bamboo is one of the most frequently used raw materials in rural communities. Bamboo needs to be utilized and processed more optimally. This is in line with the conditions in Plalangan Village, which has abundant bamboo reserves. Research on bamboo-based products requires alternatives. The purpose of creating this artwork is to find the best option for processing bamboo into other alternatives to maximize the product. One solution is to make bamboo-based products using weaving techniques. This is important as the main capital so that the artwork/product can be included in the management of surrounding natural resources. The methods used in creating this work are reflection, exploration, elimination, realization, and awareness. The techniques used are cross weaving with a choice of square, pentagonal, and hexagonal shapes. These techniques can be used to form tubes, cubes, or other shapes according to product needs, such as living room and bedroom lamps, displays, or contemporary installations.